Effect of cassavabased cropping systems on physicochemical properties of soil and earthworm casts in a tropical Alfisol - Hulugalle, N.R.; Ezuma, H.C. (Elsevier, 1991)
The effects of cassava-based intercropping systems and rotations on physical and chemical properties of earthworm casts and the adjacent soil were studied on an Oxic Paleustalf in south-western Nigeria. Earthworm activity was greater with intercropping although it was not significantly affected by the number of component crops in a mixture. The particle size distribution, bulk density, exchangeable cations, Bray-1-P, pH and effective cation exchange capacity (CEC) of soil and earthworm casts did not differ among the cassava-based cropping systems investigated. Greatest values of mean weight diameter, organic C and total N were observed in earthworm casts from three component crop mixtures, although the adjacent soil was not similarly affected. The results suggest that although the cropping system changed some physico-chemical properties of earthworm casts, similar changes did not occur in the adjacent soil. Water infiltration into the soil was, however, increased by intercropping and may be related to earthworm activity. Cropping system may, therefore, influence soil fertility indirectly by changing water infiltration characteristics and hence, nutrient losses in run-off and erosion. In relation to soil, earthworm casts had higher silt and clay contents, bulk density, mean weight diameter, pH, Bray-1-P, Organic C, total N, C:N ratio, exchangeable cations and effective CEC, and lower sand content.